The Human Security Implications of the Nigeria’s Counter-Insurgency Strategy against Boko Haram - Zango, AbdulAziz Sani (Kashere Journal of Politics and International Relations, 2024)
The spate of violent attacks perpetrated by Boko Haram insurgents has necessitated the response by the Nigerian State through counterinsurgency measures. However, this has negativeliy affected the human security of the affected communities in the northeast region. This paper examines the counter-insurgency strategy adopt by the Nigerian state in responding to Boko Haram insurgency and human security implications in the state. Library research is used as a methodology of the paper. The paper advances the arguement that even though counter-insurgency measures adopted by the Nigerian in its fight against Boko Haram proves effective from the onset, yet it fail to completely defeat and eliminate the movement, and instead the measures breed a renewed upraise of the movement with more sophisticated waves of armed violence against the state and its security apparatus, and gross human rights violations and human security implications against the civilian population. Thus, the paper conclude that as long as these counter-insurgency strategy remain the only measure of fighting against Boko Haram insurgency it could hardly be possible to have lasting solution to this security challenges. In view, of this, the paper recommends adopting a more pragmatic peaceful approach revolving around dialogue and peace-building that is less militaristic in dealing with problem, human security considerations should be emphasised.